Drosophila melanogaster as a model for basal body research - Jana, Swadhin Chandra (2016)
The fruit fly, Drosophila melanogaster, is one of the most extensively studied organisms in biological research and has centrioles/basal bodies and cilia that can be modelled to investigate their functions in animals generally. Centrioles are nine-fold symmetrical microtubule-based cylindrical structures required to form centrosomes and also to nucleate the formation of cilia and flagella. When they function to template cilia, centrioles transition into basal bodies. The fruit fly has various types of basal bodies and cilia, which are needed for sensory neuron and sperm function. Genetics, cell biology and behaviour studies in the fruit fly have unveiled new basal body components and revealed different modes of assembly and functions of basal bodies that are conserved in many other organisms, including human, green algae and plasmodium. Here we describe the various basal bodies of Drosophila, what is known about their composition, structure and function.